Determinação do período de receptividade do estigma e liberação de pólen em cultivares de nogueira-pecã (Carya illinoinensis K.) cultivadas em Cachoeira do Sul e Santa Maria (RS) - Hamann, Jonas Janner (2018)
Pecan (Carya illinoinensis) is commercially cultivated in USA, México, Australia, South Africa, Argentina, Uruguay and Brazil. This is a species that has dichogamy, a sort of biological phenomenon where the staminate inflorescence matures in a different period than the pistillate inflorescence which naturally reduces the occurrence of self-pollinization. Dichogamy makes it necessary to plant pollinating cultivars in a commercial pecã orchard. In Brazil, the only research on the flowering period of pecã was carried out for more than three decades, but the most of these cultivars are not longer grown commercially. With the constant increase of the area cultivated with pecã the determination of the receptivity period of the stigma and release of pollen has fundamental importance for a high pollination and productivity of nuts. The pollination period of ten pecã cultivars grown commercially in RS, Brazil in the years 2016 and 2017, was determined in Cachoeira do Sul and Santa Maria. The results showed that there are differences in its flowering periods between the two years and sites. In 2017, when the temperature in September was higher in both municipalities (Cachoeira do Sul and Santa Maria), there was a anticipation in the release of pollen and receptivity of the stigma of the most cultivars, but cv. Barton maintained practically the same behavior in the orchard located in Cachoeira do Sul and Santa Maria, in both years. It can be concluded that the current recommendation of cultivar for pollinization elaborated by nurseries and the technicians related to brazilian pecã industry should be renewed for the principal cv. Barton. The cultivars Cape Fear, Chickasaw, Desirable and Success did not pollinate cv. Barton in the two years in Cachoeira do Sul and the cultivars Cape Fear and Chickasaw did not pollinate the cv. Barton in neither of the two years in Santa Maria.